(untitled) (World Bulletin of Management and Law, 2023)
The place of digital technologies in the modern economy is now becoming increasingly obvious. Information and communication technologies are widely employed in a variety of industries, including banking, government, business, healthcare, and security. This suggests that contemporary information and communication technology have been fully and consistently incorporated into all facets and regions of our society. In light of this, numerous projects aimed at bringing modern technology to our nation are in progress. This suggests that the wide implementation of modern information and communication technologies in our society, as well as its application in practice, provides an opportunity for the wide introduction of digital technologies in all spheres. This article provides feedback and feedback on the role of Information Communication Technologies in management.